Significance of fluid chemistry throughout diagenesis of aragonitic Porites corals – An experimental approach. (1st August 2019) - Pederson, Chelsea L.; Weiss, Leonie; Mavromatis, Vasileios; Rollion‐Bard, Claire; Dietzel, Martin; Neuser, Rolf; Immenhauser, Adrian
Abstract: Marine carbonates are among the most important archives of environmental information in both modern and past environments. Widely used but particularly sensitive archives are the aragonitic skeletons of scleractinian corals. However, due to the metastable nature of aragonite, a multitude of chemical, mineralogical, and (micro)biological processes can lead to diagenetic alteration of these archives and their proxy information can be altered or lost. Here, hydrothermal alteration experiments were performed to create a better understanding of the diagenesis of an often‐utilized genus, Porites . Same‐specimen subsamples were heated in two fluid types and at two temperatures and durations, and their resulting alteration features were assessed to allow insight to the mechanisms and drivers of diagenetic modification. Experiments with fluid temperatures of 130°C induced remobilization and darkening of organic matrices, with no other evidence for alteration observed. In contrast, specimens exposed to a temperature of 160°C underwent significant diagenetic alteration dependent on fluid type. Fluid chemistry, particularly Mg/Ca ratios, was found to regulate the type of alteration (e.g. neomorphism or reprecipitation). Reaction with meteoric water resulted in almost complete neomorphism of the aragonite skeleton to blocky calcite, as well as significant exchange with the experimental fluid. In comparison, samples altered in the experimental burial fluids record no mineralogic or significant isotopic change, but instead, small‐scale dissolution–reprecipitation of the primary skeleton, along with the precipitation of pore‐filling aragonitic needle cements was observed. The δ 18 Ocarbonate data indicate transformation via dissolution–reprecipitation mechanisms depending on the degree and mechanism of diagenesis, and are strongly dependent on fluid chemistry. The main outcome of this work is that a multi‐proxy approach has the best potential to shed light on the interpretation of processes and pathways of aragonitic coral alteration. This study has implications for early alteration of carbonate archives within varying diagenetic fluids, with results aiding in the identification of past burial conditions. Abstract : Hydrothermal alteration experiments were performed to create a better understanding of the diagenesis of an often‐utilized species, Porites. Alteration with meteoric waters resulted in almost complete neomorphism of the aragonite skeleton to blocky calcite, as well as significant isotopic exchange with the experimental fluid. In comparison, samples altered in the experimental burial fluids record no major mineralogic change or significant isotopic exchange, but instead, the precipitation of pore‐filling aragonitic needle cements was observed.